Back Cover: Coordination Behavior of [Cp′′2Zr(η1:1‐P4)] towards Different Lewis Acids (Chem. Eur. J. 43/2017). Issue 43 (4th July 2017) - Seitz, Andreas E.; Vogel, Ulf; Eberl, Miriam; Eckhardt, Maria; Balázs, Gábor; Peresypkina, Eugenia V.; Bodensteiner, Michael; Zabel, Manfred; Scheer, Manfred
Abstract : The versatile coordination behavior of [Cp′′2 Zr(η 1:1 ‐P4 )] is investigated. Lewis acidic fragments of tungsten, manganese, iron and aluminum are used to study their influence on the coordination behavior towards [Cp′′2 Zr(η 1:1 ‐P4 )], which strongly depends on the steric and electronic properties of the used Lewis acids. The cover picture highlights these results showing a [Cp′′2 Zr(η 1:1 ‐P4 )] molecule, on the basis of which to decide which hiking trail to take. More information can be found in the Full Paper by M. Scheer et al. onpage 10319 .